2019
DOI: 10.1177/0954411919898011
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bacterial adhesion on zirconium-based bulk metallic glasses by femtosecond laser nanostructuring

Abstract: As high-performing materials, bulk metallic glasses have attracted widespread attention for biomedical applications. Herein, the bacterial adhesion properties of femtosecond laser-nanostructured surfaces of four types of zirconium-based bulk metallic glasses are assessed. Laser-induced periodical surface structures and nanoparticle structures were fabricated by femtosecond laser irradiation under different energy intensities (0.23 and 2.3 J/mm2). Surface topography, roughness, wettability, and surface energy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Nanometric surfaces were inspired by antibacterial activities seen in nature, such as those that occur in lotuses, cicadae, sharks, butterflies, and among others, dragonfly wings [ 35 , 52 ]. Recent studies [ 75 , 76 ] attempt to replicate these patterns by developing surfaces for future application in the biomedical field, such as PMMA surfaces designed as shark skin-patterned [ 75 ], and zirconium-based bulk metallic glasses [ 76 ]. However, this area of research is still in its infancy and further studies are needed before these materials can be used.…”
Section: Strategies For Interrupting Biofilm Formationmentioning
confidence: 99%
“…Nanometric surfaces were inspired by antibacterial activities seen in nature, such as those that occur in lotuses, cicadae, sharks, butterflies, and among others, dragonfly wings [ 35 , 52 ]. Recent studies [ 75 , 76 ] attempt to replicate these patterns by developing surfaces for future application in the biomedical field, such as PMMA surfaces designed as shark skin-patterned [ 75 ], and zirconium-based bulk metallic glasses [ 76 ]. However, this area of research is still in its infancy and further studies are needed before these materials can be used.…”
Section: Strategies For Interrupting Biofilm Formationmentioning
confidence: 99%
“…An alternative approach is to modify the morphology, chemical composition and microstructure of the surface of Zr-based BMGs. Du and co-researchers [22] successfully reduced E. coli and S. aureus bacterial adhesion on Zr-based BMGs by femtosecond laser surface patterning, whilst having no effect on mammalian cell viability. Haratin et al [23] shown improved surface hardness of (Zr 55 Cu 30 Al 10 Ni 5 ) 98 Er 2 BMG from~600 to~1200HV using gaseous oxidising treatment, in which case a topmost Cu-rich zone formed on the surface oxide.…”
Section: Potential Solutions Limitations and Research Aimmentioning
confidence: 99%
“…Various theoretical approaches have been applied to explain the LIPSS occurrence, including the scattering-interference mechanism, excitation of surface electromagnetic waves (polaritons, plasmons), counter-propagating surface plasmons, and material reorganization [ 3 , 4 , 5 ]. Although a comprehensive theoretical picture is still in development, LIPSS attract research attention due to the remarkable simplicity and reliability of the single-step technique of patterning the surface with subwavelength periodic features suggesting a wide range of possible applications, such as surface colorization, reflection/transmission tuning, wettability and friction control, security marking, energy storage and solar cells efficiency enhancement, biosensing, living cell growth and adhesion control, and more [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%